Genomic characterization of blaVIM-11-harbouring plasmids recovered from Pseudomonas aeruginosa - Elena, Alan (2024)
Objectives: To the best of our knowledge, no genomic descriptions of blaVIM-11-harbouring plasmids are available in literature so far. The aim of this study was to describe the genomic features of three blaVIM-11-harbouring plasmids recovered from Pseudomonas aeruginosa isolated in Argentina in different periods. Methods: blaVIM-11-harbouring plasmids from three clinical P. aeruginosa isolates were transferred by transformation into P. aeruginosa PAO-1. Then, genomic DNA of these transformants was extracted and sequenced using NovaSeq 6000 System-Illumina. De novo assemblies were generated using Unicycler program and reads were mapped against a reference genome of P. aeruginosa PAO-1. Plasmids sequences were predicted identifying the reads that did not map the reference sequence of PAO-1. These reads were recovered and assembled de novo. In silico predictions were carried out using bioinformatics tools. Results: One Plasmid (pP6VIM-11) was distributed in 2 contigs, a second plasmid (pPOta2VIM-11) was found in a single contig, and the last one (pP936401VIM-11) was fragmented into 4 contigs. pP6VIM-11 and pPOta2VIM-11 belonged to the IncP-1β group, displaying 64% of coverage and 83.9% of identity among them. pP936401VIM-1 plasmid corresponded to the IncN group. The bioinformatic analysis revealed that blaVIM-11 was located in a class 1 integron, flanked by insertion sequences, exhibiting potential for its dissemination. However, none of the plasmids were conjugative. Conclusion: This study corresponded to the first description and deposit of blaVIM-11-harbouring plasmids in P. aeruginosa, which expands the limited knowledge about their molecular epidemiology.